Resounding Meaning: A PERMA Wellbeing Profile of Classical Musicians - Ascenso, Sara; Perkins, Rosie; Williamon, Aaron (Frontiers in Psychology, 2018)
While music has been linked with enhanced wellbeing across a wide variety of contexts, the professional pursuit of a music career is frequently associated with poor psychological health. Most research has focused on assessing negative functioning, and to date, few studies have attempted to profile musicians’ wellbeing using a positive framework. This study aimed to generate a profile that represents indicators of optimal functioning among classical musicians. The PERMA model, which reconciles hedonic and eudaimonic wellbeing, was adopted and its five elements assessed with a sample of professional classical musicians: Positive Emotion, Engagement, Relationships, Meaning and Accomplishment. 601 participants (298 women, 303 men) engaged in careers as orchestral (n=236), solo (n=158), chamber (n=112) and choral musicians (n=36), as well as composers (n=30) and conductors (n=29), answered the PERMA-Profiler, a self-report questionnaire built to assess the five components of PERMA. Results point to high scores across all dimensions, with Meaning emerging as the highest rated dimension. Musicians scored higher than general population indicators on Positive Emotion, Relationships and Meaning. When wellbeing is assessed as positive functioning and not the absence of illbeing, musicians show promising profiles. The reconciliation between these findings and the previous body of research pointing to the music profession as highly challenging for healthy psychological functioning is discussed.